The Combined Influence of Oral Contraceptives and Human Papillomavirus Virus on Cutaneous Squamous Cell Carcinoma - Efird, Jimmy T.; Toland, Amanda E.; Lea, C. Suzanne; Phillips, Christopher J. (My University, 2011)
The vast majority of cutaneous squamous cell carcinoma (CSCC) will occur in those with fair complexion, tendency to burn, and high ultraviolet radiation (UVR) exposure. Organ transplant recipients also are an important population at great risk for CSCC. An association has been reported between oral contraceptive (OC) use, human papillomavirus virus (HPV) and cervical cancer, and there could be a similar association for CSCC. The cutaneous HPV β-E6 protein, a close cousin of the transformative E6 protein underlying anogenital cancers, has been shown to inhibit apoptosis in response to UVR damage and stimulate morphologic transformation in rodent fibroblast cell lines. Furthermore, OC use has been shown to enhance HPV transcription and may contribute to CSCC risk through this pathway.
Keywords: cutaneous squamous cell carcinoma; human papillomavirus virus; oral contraceptives